MENERUSKAN HIDUP SETELAH KERUSUHAN: INGATAN KOLEKTIF DAN IDENTITAS ETNIS MADURA PASCA KEKERASAN ANTARETNIS DI KOTA SAMPIT, KALIMANTAN TENGAH - Yogaswara, Herry (Masyarakat Indonesia, 2018)
The PhD dissertation project is about to explore Maduranese who returned to Sampit after the communal violence of February 2001. Sampit is a small town in the district of Kotawaringin Timur of the province Central Kalimantan, Indonesia. The communal violence well known as kerusuhan or riot started from February 18, 2001 in the town of Sampit and spill-over to other city and districts in Central Kalimantan. Hundred peoples were killed, mostly Maduranese and thousands Madurenese leave Central Kalimantan by forced. They became internally displace person (IDP) in several districts and cities in Southern Kalimantan and East Java, mostly in the Madura Island. The framework of this thesis is relationship among collective memory, historicity and identity. The thesis would like to confirmed hypothesis which collective memory is shaping identity. Locus of study was town of Sampit, in the district of Kotawaringin Timur. However, to have wider perspective, the researcher visited city and other districts in Central Kalimantan; districts in South Kalimantan as neighbor province and Madura island in East Java. Result of the research are understanding narratives of riots including waves of migration in and out of Sampit; causes of riot; identities of Maduranese and efforts of Maduranese returned to Sampit. Collective memory is a strategy for Maduranese returned to Sampit through mechanism of remembering and forgetting.